Hypervelocity Stars Track Back to the Galactic Center in Gaia DR3 - Liao, Jiwei; Du, Cuihua; Li, Hefan; Ma, Jun; Shi, Jianrong (Astrophysical journal. Letters, 2023)
Based on the proper motions and radial velocities from Gaia Data Release 3, we identify two hypervelocity stars (HVSs) that may originate from the Galactic center (GC). We select the candidates by first filtering for all Gaia stars with Galactocentric radial velocities >500 km s −1 . We also require the candidates cross the Galactic midplane only once at 80% confidence, as determined by backwards orbit integration in several models of the Galactic potential, given the uncertainties in the Gaia measurables. The final two HVS candidates are the only such stars in our sample whose backwards-integrated trajectories pass within 1 kpc of the GC, suggesting a potential GC origin. We discuss possible ejection scenarios for these HVSs, in particular, by finding that ejection via the Hills mechanism is unlikely unless the HVS trajectories were significantly altered by local or large-scale perturbations to the assumed Galactic potential, e.g., the Large Magellanic Cloud. Interestingly, one of the HVSs ejects in a direction that is curiously aligned with the clockwise stellar disk around Sgr A*, suggesting a possible connection. We also discuss that the two stars may be ejected by other mechanisms.